HUBUNGAN JENIS SUPLEMEN YANG DIKONSUMSI DENGAN USIA KEHAMILAN, LAMA PERSALINAN, DAN JENIS PERSALINAN - Isnaini Fajariah; Triska Susila Nindya; Sri Sumarmi (Media Gizi Indonesia, 2015)
Women labor process consists of several stages which each of it has risk to unspontaneous labor that need assistance, such as vaccum, induction, forcep, and section caesarean. The risk could be worsened by maternal anemia or low Hb concentration. Reducing anemia can be done by iron and folic acid (IFA) and multimicronutrients (MMN) supplementation. The aim of this study is to analyze the correlation between type of supplement with gestational age, duration of labor, and type of labor. The study design used was cross sectional. The population is mother in delivery who has given the supplement when they were pregnant. The population were spread in 9 sub-districts in Probolinggo district. The sample was 60 respondents that selected by simple random sampling. Data analysis used was chi square. The result showed that the duration of respondents’ labor, both IFA (73.3%) or MMN (83,3%) were in aterm category, that is 37-42 weeks. Duration of labor was categorized in non-prolonged labor or less than 24 hours (IFA=100%, MMN=93.3%). The most common type of labor is spontaneous without assistance (IFA=70.0%, MMN=66.7%). There is no correlation between type of supplement with gestational age (p = 0,144), duration of labor (p = 0,492), and type of labor (p = 0,492). This research suggest that further research should be carried out regarding factors that strongly effect gestational age, duration of labor, and types of labor such as Hb level, consumption pattern, and supplement consumption methods.Keywords: duration of labor, gestational age, supplement, type of labor